Design and thermodynamic modeling of a renewable energy based plant for hydrogen production and compression. (2nd October 2020) - Yilmaz, Fatih; Ozturk, Murat; Selbas, Resat
Abstract: In the examined paper, a solar and wind energy supported integrated cycle is designed to produce clean power and hydrogen with the basis of a sustainable and environmentally benign. The modeled study mainly comprises of four subsystems; a solar collector cycle which operates with Therminol VP1 working fluid, an organic Rankine cycle which runs with R744 fluid, a wind turbine as well as hydrogen generation and compression unit. The main target of this work is to investigate a thermodynamic evaluation of the integrated system based on the 1st and 2 nd laws of thermodynamics. Energetic and exergetic efficiencies, hydrogen and electricity generation rates, and irreversibility for the planned cycle and subsystems are investigated according to different parameters, for example, solar radiation flux, reference temperature, and wind speed. The obtained results demonstration that the whole energy and exergy performances of the modeled plant are 0.21 and 0.16. Additionally, the hydrogen generation rate is found as 0.001457 kg/s, and the highest irreversibility rate is shown in the heat exchanger subcomponents. Also, the net power production rate found to be 195.9 kW and 326.5 kW, respectively, with organic Rankine cycle and wind turbine. The final consequences obtained from this work show that the examined plant is an environmentally friendly option, which in terms of the system's performance and viable, for electrical power and hydrogen production using renewable energy sources. Highlights: A solar and wind energy based integrated system is proposed and evaluated. Renewable energy-assisted hydrogen and power production is investigated. The detailed performance evaluation of the system is done through energetic and exergetic assessment. The energy and exergy efficiencies of the whole system are determined as 0.21 and 0.16, respectively.